EFEKTIVITAS KERJASAMA GURU DAN ORANG TUA DALAM MENDUKUNG PEMBELAJARAN BACA AL-QURAN ANAK DI SD IT NURUL ISHLAH BANDA ACEH - Dwi Pratiningsih (Jurnal Ilmiah Didaktika, 2017)
Cooperation of teacher-parents is essential in stimulating the development of children’s abilities, especially the ability to read the Quran. This research focuses on: (1) What are the forms of cooperation of teachers-parents in supporting students’ learning of reading the Quran at the Integrated Islamic Primary School SDIT Nurul Ishlah, Banda Aceh; (2) How is the effectiveness of the cooperation of teacher-parents in supporting students’ learning of reading the Quran at the school? (3) What are the obstacles encountered in the implementation of the cooperation of teachers and parents? This is by nature mixed research. Observations, interviews, questionnaires, and document analysis were used in collecting data. The data were analyzed descriptively. The results show that there have been many kinds of collaborative efforts of teacher-parents, such as meeting of teacher-parents, seminars of parenting, monitoring book of the students’ tahsīn/tahfīẓ of the Quran, personal communication, and parents’ participation in learning to read the Quran at home. All these have been effective. Nevertheless, some constraints exist in the implementation of the cooperation, including the lack of attention and concern of some parents, and the lack of facilities and infrastructure that support the programs.